Oxidative stress evaluation of ischemia and reperfusion in kidneys under various degrees of hypothermia in rats - Santos,Emanuel Burck dos (2013)
PURPOSE:To design an animal model of ischemia-reperfusion (I/R) in kidneys and evaluate the role that predetermined ranges of local hypothermia plays on markers of stress-oxydative as well as on histologic sections. METHODS: Twenty eight male rats Wistar, under general anesthesia, undergone right nephrectomy (G0, control group) followed by left kidney ischemia during 40 min. Four temperatures groups were designed, with seven animals randomized for each group: normothermic (G1, ±37ºC), mild hypothermia (G2, 26ºC), moderate hypothermia (G3, 15ºC) and deep hypothermia (G4, 4ºC). Left kidney temperature was assessed with an intraparenchymal probe. Left nephrectomy was performed after 240 min of reperfusion. After I/R a blood sample was obtained for f2-IP. Half of each kidney was sent to pathological evaluation and half to analyze CAT, SOD, TBARS, NO3, NO2. RESULTS:Histopathology showed that all kidneys under I/R were significantly more injured than the G0 (p<0.001). TBARS had increased levels in all I/R groups compared with the G0 (p<0.001). CAT had a significant difference (p<0.03) between G1 and G4. Finally, no difference was found on SOD, NO3, NO2 nor on f2-IP. CONCLUSION: This model of I/R was efficient to produce oxidative-stress in the kidney, showing that 4ºC offered significant decrease in free radicals production, although tissue protection was not observed.